HIV Care Outcomes in Relation to Racial Redlining and Structural Factors Affecting Medical Care Access Among Black and White Persons with Diagnosed HIV—United States, 2017. - Logan, J.; Crepaz, Nicole; Luo, Feijun; Dong, Xueyuan; Gant, Zanetta; Ertl, Allison; Girod, Candace; Patel, Nimeshkumar; Jin, Chan; Balaji, Alexandra; Sweeney, Patricia (AIDS & Behavior, 2022)
Black/African American (Black) versus White persons are unequally burdened by human immunodeficiency virus (HIV) in the United States. Structural factors can influence social determinants of health, key components in reducing HIV-related health inequality by race. This analysis examined HIV care outcomes among Black and White persons with diagnosed HIV (PWDH) in relation to three structural factors: racial redlining, Medicaid expansion, and Ryan White HIV/AIDS Program (RWHAP) use. Using National HIV Surveillance System, U.S. Census, and Home Mortgage Disclosure Act data, we examined linkage to HIV care and viral suppression (i.e., viral load < 200 copies/mL) in relation to the structural factors among 12,996 Black and White PWDH with HIV diagnosed in 2017/alive at year-end 2018, aged ≥ 18 years, and residing in 38 U.S. jurisdictions with complete laboratory data, geocoding, and census tract-level redlining indexes. Compared to White PWDH, a lower proportion of Black PWDH were linked to HIV care within 1 month after diagnosis and were virally suppressed in 2018. Redlining was not associated with the HIV care outcomes. A higher prevalence of PWDH residing (v. not residing) in states with Medicaid expansion were linked to HIV care ≤ 1 month after diagnosis. A higher prevalence of those residing (v. not residing) in states with > 50% of PWDH in RWHAP had viral suppression. Direct exposure to redlining was not associated with poor HIV care outcomes. Structural factors that reduce the financial burden of HIV care and improve care access like Medicaid expansion and RWHAP might improve HIV care outcomes of PWDH.